К флоре Bacillariophyceae побережья Тауйской губы Охотского моря (Россия) - Харитонов, В.Г. (Альгология, 2011)
Дополнен список диатомовых водорослей побережья Тауйской губы. На сегодняшний день общий список диатомовых водорослей составляет 689 видов (755 таксонов видового и внутривидового ранга), относящихся к 103 родам; 520 видов и разновидностей представлены впервые. In 2005 a collective monograph "Biological Diversity of the Tauyskaya Guba coast of the Okhotsk Sea" was published. One of the parts of the book was devoted to diatoms found in water bodies along the Tauyskaya Guba coast (Kharitonov, 2005). In this part of the monograph for the first time the author presents 235 diatom taxa united in 40 genera in a form of a brief annotated list. Order Centrales includes 14 genera and 57 taxa of species and subspecies ranks; order Penales with Fragilariaceae and Achnanthaceae families include 26 and 178 correspondingly. The other diatom groups found in water bodies along the coast were at that time under analysis and were not presented in the book. The present work is intended to fill this gap in our knowledge. The total list of diatoms found in water bodies of Tauyskaya Guba water basin includes 689 species (755 taxa of species and subspecies ranks) belonging to 103 genera. 520 species and subspecies are presented in the present work for the first time. Работа выполнена при финансовой поддержке гранта ДВО РАН, проект 06-1-П11-036.